2012
DOI: 10.1111/apa.12034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Helping Babies Breathe: training for healthcare workers at hospitals in Rwanda

Abstract: Healthcare workers who participate in a Helping Babies Breathe programme can significantly improve their knowledge. While such knowledge is retained for at least 3 months, skills dropped to unsatisfactory levels in that period of time, indicating the need for retraining in the interim or the acquisition of practical experience by such healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 21 publications
10
57
1
Order By: Relevance
“…The fact that there was sustainment in ‘FMV within the Golden Minute’, and in FMV skills of the VMWs from 3 to 12 months, is in contrast to the findings of Musafili et al 18 where the number of participants passing and the OSCE scores decreased 3 months post HBB training. Our positive observations may be partly related to the fact that the NeoNatalie simulator kit was made available to the VMWs for practice during their bi-weekly visits to their local medical centre.…”
Section: Discussioncontrasting
confidence: 94%
“…The fact that there was sustainment in ‘FMV within the Golden Minute’, and in FMV skills of the VMWs from 3 to 12 months, is in contrast to the findings of Musafili et al 18 where the number of participants passing and the OSCE scores decreased 3 months post HBB training. Our positive observations may be partly related to the fact that the NeoNatalie simulator kit was made available to the VMWs for practice during their bi-weekly visits to their local medical centre.…”
Section: Discussioncontrasting
confidence: 94%
“…Five (50.0%) of these studies showed significant performance falloff over the time period analyzed. 37,38,48,56,66 Three studies (30.0%) showed no falloff 41,43,52 ; the 2 remaining studies (20.0%), both from Ethiopia, found varying levels of retention in different groups of birth attendants, with higher levels of training associated with less falloff. 55,67 These latter 5 studies showing either no falloff or mixed results included the 4 longest running studies in our literature review, ranging from 9 months to 2 years.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
“…The program includes a validated simulation evaluation tool called an Objective Structured Clinical Examination (OSCE) [3,4]. Several studies have demonstrated trainee improvement on the examination using a pre-post design [58]. However, evidence also suggests performance decreases significantly over time when learners are not provided with ongoing refresher training [9,10].…”
Section: Introductionmentioning
confidence: 99%